The chlorophyll contents and growth performances of West Java (Indonesia) jobtears (Coix lacryma-jobi) accessions under low light intensity conditions - Titi Juhaeti; NINIK SETYOWATI; FAUZIA SYARIF (Society for Indonesian Biodiversity, 2020)
Abstract. Juhaeti T, Setyowati N, Syarif F. 2020. The chlorophyll contents and growth performances of West Java (Indonesia)  jobtears (Coix lacryma-jobi) accessions under low light intensity conditions. Biodiversitas 21: 5178-5185. The research was carried out to study the shading tolerance of five jobtears (Coix lacryma-jobi L) accession collected from Bandung, Kuningan, Garut, Sukabumi, and Sumedang West Java Indonesia. The existence of shade-tolerant jobtears was important to increasing its cultivation for food diversification effort. The research was conducted in the Botany Division, Research Center for Biology, Indonesian Institute of Sciences. The experimental design was a Randomized Complete Block Design with two factors. The first factors were 0%, 25%, 50%, and 75% shading intensity. The second factors were five West Java jobtears accession, namely Bandung, Kuningan, Garut, Sukabumi, and Sumedang accession. The shading intensity set up artificially by the black plastic net. Jobtears seeds planted on planting beds on 70x100 planting distance. The variable observed included microclimate, plant growth, leaf chlorophyll content, and grain production. The result indicated that jobtears accession showed differences in growth and production characters. Low light intensity significantly affected plant growth and production. The plant height, leaf number, and chlorophyll content variables increased until 50% shading intensity and then decreased by 75% shading. Plant production decreased by the increased of shading intensity. The Bandung and Garut accessions can be determined as a potential low-light tolerant accession due to its better growth and production compared with others and the lowest percentage of decreased production. For further research, the Garut and Bandung accession can be used as a genetic biodiversity source for shading tolerance breeding efforts.